INTERACTIVE POWERPOINTS DEVELOPMENT AS LEARNING MEDIA IN IMPROVING COMMUNICATION SKILL FOR SECOND SEMESTER OF ENGLISH DEPARTMENT STUDENTS AT ABA BALIKPAPAN - Muhammad Rochman (Journey: Journal of English Language and Pedagogy, 2021)
This study aims to describe the development stage of learning media in the form of interactive multimedia powerpoints, describe the quality of the learning media developed in the form interactive multimedia powerpoint, and describe lecturer and student’s responses on the use of learning media in the form of interactive multimedia power point. This research was development research (R & D). Population of this research was the second semester of second semester of English students of ABA Balikpapan. Determination sample using random sampling technique. Based on these techniques, obtained 1 class of 4th semester students as test subjects. Data collection technique using a questionnaire in the form of a questionnaire that had be filled in by lecturers and students after using the learning media. Before being tested, the media learning through the media validation stage and material validation by media experts and material expert. The data analysis technique used descriptive qualitative, with transforming qualitative data into quantitative data. The result of this research is an interactive media of communication learning powerpoint which is packaged on a class presentation. Stages in development These media are (1) Initial data collection, (2) Product development, (3) Validation of material experts and media experts, (4) Revision, (5) Product testing, (6) Analysis data, and (7) Revision of the final product. The results of this study consist of two aspects, namely the quality of the media and responses users. In the aspect of media quality, the assessment was carried out by media experts and experts Theory. In the aspect of user responses, the assessment was carried out by lecturer and students. Assessment by media experts got a percentage of 63%. Expert assessment material gets a percentage of 90%. Assessment by subject lecturers get a percentage of 83%. Assessment by students gets a percentage amounted to 65.5%. The overall average rating was 75%. Result of this research proves that this powerpoints learning media is feasible to use based on validation tests by material experts and media experts.